Transport activity of the multidrug resistance protein is accompanied by amiloride-sensitive intracellular pH changes in rat hepatoma cells - García Cañero, Rafael; Pérez de Diego, Javier; Trilla, C.; Cobo, J.M.; Díaz-Gil, J. (My University, 2024)
Rat hepatoma cells (HTC) maintain a resting intracellular pH (pH(i)) close to 7.22±0.05 (n = 10), well above the set point for Na+ :H+ exchange (pH(i) = 6.88±0.009; n = 6) and below the pH of the extracellular medium. HTC cells present inwardly and outwardly-directed Na+(H+) and K+ electrochemical gradients. Changes in pH(i) are sensitive to amiloride. Gp170 protein is immunodetectable in HTC plasma membranes, and amiloride and verapamil, separately or together, diminish the efflux of rhodamine 123 (Rhod 123), a model substrate of this protein, from previously loaded cells. Amiloride increases colchicine and doxorubicin uptake and Rhod 123 retention in a dose-dependent way. On the other hand, uptake by HTC of colchicine, another substrate of Gp170, is increased by ATP deprivation and inhibition of protein kinase C by staurosporine, by verapamil and by other substrates of this transporter, as observed in other Gp170 expressing cells. Addition of colchicine or verapamil to 2',7'-bis-(2-carboxyethyl)-5-(and-6-)- carboxyfluorescein acetoxymethyl ester (BCECF)-loaded HTC cells in the presence of extracellular Na (Na(e)) induces a gradual amiloride-sensitive increase in ph(i), whereas, in the absence of Na(e)+, a slow intracellular acidification, sensitive to the presence of other substrates of Gp170 and staurosporine, is promoted. Na+ :H+ antiport activity is increased in the presence of Gp170 substrates in an amiloride- sensitive way. These results indicate that multidrug resistance transport activity modifies pH(i), which in turn could be efficiently modulated by pharmacological modification of the pH(i) homeostasis in hepatoma cells through Na+ :H+ antiport inhibition.